PATTERN OF MAGNETIC RESONANCE IMAGING AND MAGNETIC RESONANCE VENOGRAPHY CHANGES IN CEREBRAL VENOUS SINUS THROMBOSIS - Zafar, Zafar A; Ali, Ali Z (Journal of Ayub Medical College Abbottabad, 2012)
Background: Cerebral venous sinus thrombosis is a common but highly under-recognised condition, which is missed not only by general practitioners but also by neurologists. Computerised tomography (CT) or magnetic resonance imaging (MRI) of brain alone is not sufficient to diagnose this condition. Objective of this study was to explore the pattern of magnetic resonance imaging (MRI) and magnetic resonance venography (MRV) changes in cerebral venous sinus thrombosis (CVST). Methods: This was a descriptive study in which 52 cases of cerebral venous sinus thrombosis with special emphasis on their MRI and MRV findings were included. The study was conducted in Neurology Unit, Lady Reading Hospital, Peshawar, Pakistan, from January 2010 to July 2011. All patients suffering from cerebral venous sinus thrombosis were included in the study. Multi-planar/multi-sequential, Tesla 1.5 MRI/MRV time of flight images were done in all cases where there was suspicion of cerebral venous sinus thrombosis. Results: Out of 52 patients with cerebral venous sinus thrombosis 41 (78.84%) were female and 11 (21.15%) were male. Mean age was 37±5 years. Definite risk factors were found in 38 (73.076%) patients with pregnancy, use of oral contraceptives or puerperium being the most frequently found risk factor in 20 (73.076%) patients. Most common complaint was headache found in 41 (78.84%) patients, followed by focal neurological deficits, and altered mental status and seizures. Papilloedema was seen in 20 (38.46%) patients. The cerebral venous sinuses most frequently involved were transverse and sigmoid sinuses in 17 patients (32.69%) while superior sagittal sinus alone in 10 (19.23%) patients. Overall CT brain was normal in 30% and MRI brain in 23.07% patients; however, MRV of these patients revealed CVST. Conclusion: Imaging plays a primary role in the diagnosis of cerebral venous sinus thrombosis because the clinical picture of CVST is non-specific and highly variable. Thrombosis of cerebral venous system is readily picked-up on MRV even if it is missed by CT scan or MRI. Keywords: Cerebral venous sinus thrombosis, CVST, Magnetic Resonance Imaging, MRI, Magnetic Resonance Venography, MRV, Computed Tomography, CT